Lung Function in Type 1 and Type 2 Diabetes Mellitus - Raju D., Dr. Srinivas; CG, Dr. Jagadesha (International Journal of Innovative Research in Medical Science, 2019)
Current estimates indicate that 8.3% of the adult population, or 71.4 million people, have diabetes in 2011, 61.3 million of whom are in India. The incidence rate for type 1 diabetes in India was frequently used in extrapolation for other countries in the region and therefore plays a pivotal role in the estimates. We evaluated the ventilatory function of type 1 diabetes mellitus and type 2 diabetes mellitus patients. Spirometry and DLCO conducted in patients who have never smoked, with no history of lower respiratory illness and at examination did not have any respiratory symptoms like nasal itching, nasal congestion, running nose, dry throat, hoarseness, epistaxis, sneezing, pain suggestive of sinusitis, cough, expectoration and dyspnea were included. DLCO <80% is statistically similar in two groups with P=0.431. Mean FEV1/FVC (measured %) according to Diabetic duration, diabetic treatment, diabetic complications and DLCO in Type II DM patents was significant. Spirometric values were consistently lower in subjects with Type 1 diabetes mellitus than in Type 2 diabetics. The effect on the FVC was even more pronounced in diabetics who had duration of disease longer than 5 years, and the effect was not explained by the difference in age alone. Subjects with poorer diabetic control have worse spirometric function. Non-enzymatic glycosylation of connective tissue, especially the collagen, may be responsible for reduced lung functions.